THE EFFECTIVENESS OF THE FUNCTION OF THE PAMONG PRAJA POLICE UNIT IN ENFORCEMENT OF REGIONAL REGULATIONS OF PUBLIC ORDER IN NORTH GORONTALO DISTRICT - Hastomo Musa; Darman; Yosef P Koton (LP2M Universitas Bina Mandiri Gorontalo, 2024)
This research aims to 1). Knowing and analyzing the effectiveness of the implementation of the Civil Service Police Unit (Satpol PP) function in enforcing the Regional Regulation on Public Order. 2). Know and analyze the factors that affect the effectiveness of Satpol PP functions in Enforcing Local Regulations on Public Order.This research uses descriptive research with a qualitative approach. Primary data sources in this study were 11 people consisting of officers at the Satpol PP Service, local government and the community and secondary data were obtained from written and digital documents relevant to the research. Data collection techniques through observation, interview guidelines and documentation. Data analysis using reduction, presentation and conclusion.The results showed that the Satpol PP function in enforcing local regulations on public order in North Gorontalo Regency was effective both in the accuracy function in determining time and objectives, the function of understanding program implementers and the function of supervising the accuracy of program targets, all three of which were running well. Meanwhile, the factors that affect the effectiveness of the Satpol PP function in enforcing regulations are still not fully effective. There are still obstacles, namely the law enforcement factor (human resources) and supporting facilities and infrastructure that are not fully adequate, such as the unavailability of permanent service offices.